Social Science As Struggle For Life and Existence Of Social Changes - Hadiani Fitri (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
Social science is a multidisciplinary field that studies human behavior, social structures, and changes in society. It encompasses disciplines such as sociology, anthropology, political science, and economics, each contributing to a deeper understanding of how individuals and societies interact. In the modern era, as the world faces rapid changes in political, economic, and cultural landscapes, social science has become increasingly vital for addressing complex global challenges. The field explores the dynamics of power, inequality, and social conflict, offering insights into ways to mitigate issues such as poverty, injustice, and discrimination. Social science research, using both qualitative and quantitative methodologies, helps in analyzing current phenomena and providing evidence-based policy recommendations. These insights are crucial for shaping effective solutions that promote social well-being at local, national, and global levels. As global issues like migration, climate change, and international conflict continue to affect societies, social science provides the tools necessary to understand and navigate these challenges. This paper discusses the scope of social science, its key disciplines, and the importance of its application in real-world problems, highlighting the need for continuous research and adaptation in response to changing societal needs.